An efficient enzymatic aminolysis for kinetic resolution of aromatic α-hydroxyl acid in non-aqueous media. Issue 48 (30th November 2016) - Chen, Shan; Liu, Fuyan; Zhang, Kuan; Huang, Hansheng; Wang, Huani; Zhou, Jiaying; Zhang, Jing; Gong, Yiwei; Zhang, Dela; Chen, Yiping; Lin, Chang; Wang, Bo
Graphical abstract: Highlights: A new and highly efficient enzymatic aminolysis approach for kinetic resolution of an array of aromatic α-hydroxy acids in non-aqueous media has been developed. In this method, anhydrous ammonia is used as the resolving agent, and the reactions can be proceeded smoothly at ambient temperatures in organic solvent. Due to the application of organic solvent and in which substrates are highly soluble, high concentrations of substrates are allowed. Excellent ee values of up to 99% and E value of up to >300 are achieved. Abstract: A new and highly efficient enzymatic aminolysis approach for kinetic resolution of aromatic α-hydroxy acid in non-aqueous media has been developed. The corresponding α-hydroxyl acid ester was employed as the substrate, and commercially available Candida antarctica lipase B is used as the biocatalyst, anhydrous ammonia is the resolving agent. Reactions can be proceeded smoothly in organic solvent at ambient temperatures. High concentration of substrate is allowed due to the application of organic media and the products are obtained in yields of up to 49% with ee values of up to 99%, and with E value of >300, representing an appealing and promising protocol for large-scale preparations.